Implementation of Moderation of Religious Life in State Senior High School 12 Semarang City - Safira Salsabila; Sutomo Sutomo; Alil Rinenggo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
SMA Negeri 12 Semarang City has religious diversity, namely 1) Islam; 2) Christianity; and 3) Catholicism, making the school one of the targets of the National Medium-Term Development Plan 2024 to increase the index of harmony between religious communities through education. The focus and purpose of the research is to describe in detail the implementation of moderation of religious life in SMA Negeri 12 Semarang City. This research uses a qualitative approach with descriptive methods. The researcher had a role in collecting data by using observation, interview, and documentation methods. This research uses an interactive model data analysis technique which then uses source and technique triangulation for validity. The results showed that the implementation of moderation in SMA Negeri 12 Semarang City has been carried out well, this can be seen from the achievement of moderation indicators, namely 1) National Commitment of the Pancasila Student Profile Strengthening Project (P5), Pancasila Education (PP) learning, Religious learning, flag ceremony and character camp; 2) Tolerance of P5, Religious and PP learning, Healthy School Movement programme, and Child Friendly Education Unit; 3) Anti-violence of P5 and punitive measures in the form of warnings, advice, point deductions, and mediation with the result that cases that cannot be handled are expelled from school; 4) Local Cultural Accommodation of P5 and extracurricular activities in the form of traditional dance.